The effectiveness of positive group psychotherapy on increasing resilience, reducing anxiety and burnout among nurses of the Covid-19 care department - Hamed Ghodsi; Shahed Masoudi; Hossein Ebrahimi Moghadam (روانشناسی و روانپزشکی شناخت, 2025)
Introduction: The COVID-19 pandemic has led to numerous challenges in recent years, many of which have persisted even after recovery from the illness. Aim: This study aimed to investigate the effectiveness of group-based positive psychotherapy in enhancing resilience and reducing COVID-19-related anxiety and job burnout among nurses working in COVID-19 care units. Method: This study employed a quasi-experimental design with pre-test and post-test measures, including an experimental group and a control group. The statistical population comprised nurses working in the COVID-19 intensive care units of Qaem and Shariati Hospitals in Mashhad between the years 2021–2022. A total of 26 eligible participants were selected through purposive sampling and randomly assigned to either the experimental group (positive psychotherapy, n = 13) or the control group (n = 13). Data collection instruments included the Connor-Davidson Resilience Scale (2003), the Corona Anxiety Scale developed by Alipour, Gadami, Alipour, and Abdulzadeh (2018), and Maslach’s Job Burnout Inventory (1981). The intervention group received eight weekly sessions of group-based positive psychotherapy, each lasting 90 minutes. Data were analyzed using univariate analysis of covariance (ANCOVA). Results: The results indicated that positive group therapy had a significant impact on increasing resilience (F = 167.614), reducing COVID-19-related anxiety (F = 5.762), and decreasing job burnout (F = 39.975) among nurses working in COVID-19 care units.